Stage of the Product Life Cycle, Business Strategy, and Business Performance - Anderson, Carl R.; Zeithaml, Carl P. (Academy of Management Journal, 1984)
This study empirically examines differences in strategic variables between stages of the product life cycle (PLC), as well as differences among the determinants of high performance across stages of the PLC. The results support the use of the PLC as a contingency variable during strategy formulation. Implications for increasing market share and ROI are discussed.